Análisis multivariante de los horizontes orgánico-minerales de los suelos del Parque Natural de Sierra Mágina (Jaén) - Liébanas, G.M.; Delgado, G.; Delgado, R.; Calero, J.; Peña, R.; Martín García, J.M.; Aranda, V. (Journal of Iberian Geology, 2002)
Soils are described normally using a great number of properties (variables). This generates a great quantity of data not easily understandable in a direct way. Consequently, multivariate analysis is necessary to support and confirm impressions and interpretations of investigations in field and laboratory. In the present work we quantify, through multivariate analysis, the relative influence of the different factors of soil formation that act on the soil system. We have studied 203 organo-mineral horizons, sampled to a depth between 0 and 25 cm of soils in the Sierra Mágina natural park (Jaén, Spain). The studied soils are from calcareous rocks. Five factors were found to be significant and showed that the organic carbon accumulation, decarbonatation and the argillization/rubefacction, as internal variables, and the hill slope, as external variable, they are those which explain a greater percentage of the natural variability of the soil system.